2003
DOI: 10.1161/01.cir.0000101927.70100.41
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Nucleoside Transport Is Required for Delivery of Intraarterial Adenosine Into the Interstitium

Abstract: Background-Adenosine, a known mediator of preconditioning, has been infused into the coronary circulation to induce therapeutic preconditioning, eg, in preparation for angioplasty. However, results have been disappointing. We tested the hypothesis that endothelial nucleoside transporter acts as a barrier impeding the delivery of intravascular adenosine into the underlying myocardium and that this can be overcome with dipyridamole, a nucleoside transporter blocker. Methods and Results-We infused saline or adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…We used a sensitive and specific ion-pair liquid chromatographic electrospray ionization tandem mass spectrometry assay to measure adenosine concentrations as described previously (Gamboa et al, 2003). HMEC-1 were placed in hypoxic chambers and incubated in serum-free DMEM containing 5 M EHNA under normoxic or hypoxic conditions for 1 h. Cell culture media were collected by centrifugation at 12,000g for 1 min at 4°C, diluted 10-fold with water containing 10 nM [U-13 C 10 -U-15 N 5 ]adenosine as an internal standard and precleared by filtration through Amicon Ultrafree-MS centrifugal filters (Millipore Corporation, Bedford, MA).…”
Section: Measurement Of Adenosine Concentrations In Hmec-1 Conditionementioning
confidence: 99%
“…We used a sensitive and specific ion-pair liquid chromatographic electrospray ionization tandem mass spectrometry assay to measure adenosine concentrations as described previously (Gamboa et al, 2003). HMEC-1 were placed in hypoxic chambers and incubated in serum-free DMEM containing 5 M EHNA under normoxic or hypoxic conditions for 1 h. Cell culture media were collected by centrifugation at 12,000g for 1 min at 4°C, diluted 10-fold with water containing 10 nM [U-13 C 10 -U-15 N 5 ]adenosine as an internal standard and precleared by filtration through Amicon Ultrafree-MS centrifugal filters (Millipore Corporation, Bedford, MA).…”
Section: Measurement Of Adenosine Concentrations In Hmec-1 Conditionementioning
confidence: 99%
“…Dipyridamole and nitrobenzylthioinosine, the two inhibitors of ENTs, protect the heart from ischemia/reperfusion-induced toxicity by increasing the concentration and efficacy of adenosine. Recently, Gamboa et al (2003) reported that inhibitor-sensitive nucleoside transporters (ENTs) may function as an efflux barrier to prevent intravascular adenosine into the interstitium of heart or blood vessels. Currently, there is no report regarding gender-related information on expression of nucleoside transporters in human heart.…”
Section: Tissue Distribution Of Nucleoside Transporters In Rodentsmentioning
confidence: 99%
“…PC via PKC and postconditioning via gradual restoration of pH at reperfusion up-regulate RISK and preserve viable part of the ischemic region. In order to confer pharmacological protection, novel therapeutic strategies, based on the knowledge of the ligands, of the receptors and of the intracellular signaling pathways have emerged (Addison et al, 2003;Gamboa et al, 2003;Martou et al, 2006;Andreadou et al, 2008b). Adenosine, nicorandil, tempol, coenzyme Q and other agents (Addison et al, 2003;Gamboa et al, 2003;Martou et al, 2006;Thaveau et al, 2010) have been already used as pharmacological mimetics of ischemic preconditioning.…”
Section: Pharmacological Protection Of Skeletal Muscle In the Settingmentioning
confidence: 99%
“…In order to confer pharmacological protection, novel therapeutic strategies, based on the knowledge of the ligands, of the receptors and of the intracellular signaling pathways have emerged (Addison et al, 2003;Gamboa et al, 2003;Martou et al, 2006;Andreadou et al, 2008b). Adenosine, nicorandil, tempol, coenzyme Q and other agents (Addison et al, 2003;Gamboa et al, 2003;Martou et al, 2006;Thaveau et al, 2010) have been already used as pharmacological mimetics of ischemic preconditioning. Furthermore, agents that increase RISK or directly prevent mPTP are also under investigation as postconditioning analogues (Andreadou et al, 2008a;Tsubota et al, 2010;Tran et al, 2011).…”
Section: Pharmacological Protection Of Skeletal Muscle In the Settingmentioning
confidence: 99%